1978
DOI: 10.1088/0022-3727/11/4/009
|View full text |Cite
|
Sign up to set email alerts
|

Multiple resonances in the composite bar technique for measuring Young's modulus and internal friction

Abstract: The authors discuss the multiple resonances which often complicate the composite bar technique for measuring elastic moduli and internal friction. These are interpreted as resulting from mixing of vibrational modes of the bar. A model based on this interpretation gives results qualitatively similar to those observed experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Also hindering the collection of data from the Au-Cd sample was the appearance of multiple resonances [12]. Multiple resonances are characterized by the appearance of many resonances occurring in a range where only one would be expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also hindering the collection of data from the Au-Cd sample was the appearance of multiple resonances [12]. Multiple resonances are characterized by the appearance of many resonances occurring in a range where only one would be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple resonances are characterized by the appearance of many resonances occurring in a range where only one would be expected. Simpson et al [12] have shown that multiple resonances are the result of 'mode mixing', and are most likely to occur during phase transitions. These are evident from the discontinuities in the falling temperature resonance frequency curve shown in figure 5.…”
Section: Discussionmentioning
confidence: 99%